Effects of bacterial communities on biofuel-producing microalgae: stimulation, inhibition and harvesting. (3rd March 2016) - Wang, Hui; Hill, Russell T.; Zheng, Tianling; Hu, Xiaoke; Wang, Bin
Abstract: Despite the great interest in microalgae as a potential source of biofuel to substitute for fossil fuels, little information is available on the effects of bacterial symbionts in mass algal cultivation systems. The bacterial communities associated with microalgae are a crucial factor in the process of microalgal biomass and lipid production and may stimulate or inhibit growth of biofuel-producing microalgae. In addition, we discuss here the potential use of bacteria to harvest biofuel-producing microalgae. We propose that aggregation of microalgae by bacteria to achieve >90% reductions in volume followed by centrifugation could be an economic approach for harvesting of biofuel-producing microalgae. Our aims in this review are to promote understanding of the effects of bacterial communities on microalgae and draw attention to the importance of this topic in the microalgal biofuel field.